The use of video-based performance analysis in the coaching process - Groom, R. (World Congress of Performance Analysis of Sport XII, 2018)
Performance analysis in sport has received considerable ncaiem ic interest over the past 20 years (e.g., Hughes and Franks, 1997, 2004, 2008). Typically, academic writing within the discipline has largely been locused upon technological choices, system d esi|n, patterns in sports performance data , an d the identficatiom of key performance indicators (Hughes and FranSs( 1997s 2004, 2008; James, 2006; O'Donoghue, 2010). Hughes (2005, p. 1) has suggested that performance analysis has gained a growing recognition throughout the world and is " recognised both as an academic subject and as an invaluable support mechanism in the coaching process". More recently, a growing body of reseaucn exists drawing upon a qualitative interpretive perspective, which examines the use of performance analysis in practice. For example, the early work of Groom et al. (2011) examined the pedagogical choices that underpinned the delivery of video-based feedback by elite football coaches. Groom et al. (2012) further examined how video-based feedback was delivered to elite youth football through a conversational analysis in situ. Similarly, Nelson et al. (2014) and Taylor et al. (2017) detailed how athletes in ice-hockey and field hockey, respectively, experienced videobased feedback sessions. This body of work has started to paint a rich and detailed picture of the what, how and why of coaches use of video-based performance analysis feedback, and also the what, how and why of athletes' experiences in practice. Future possibilities exist to examine how the use of technology such as `the video-wall', drones, instant mobile video messaging, telestrator technology, online performance analysis TV channels, wearable technology, data visualisation, and sports analytics to contribute towards supporting the development of the coaching process and fan engagement in the field of sports performance analysis.